Potentials of collaborative decision support methodologies to enhance reconciliation of competing forest uses—An action research on Regional Forest Programme in Finland. (September 2016) - Tikkanen, Jukka; Hujala, Teppo; Kurttila, Mikko
Highlights: Weak political capital and propensity toward status-quo are locking problems of RFP. Policy stakeholders favour discussion-oriented methods in forest programming. Futures workshops may help to overcome stakeholders' advocacy behaviour. Simple ranking and scoring techniques appear feasible for policy working groups. We propose re-definition of Forest Councils and use of dis-aggregative methodology. Abstract: Compiling forest policy at national and sub-national levels is a participatory activity that aims to achieve balance between multiple forest-use alternatives. In Finland the effectiveness and acceptability of regional forest programmes has been doubted. The quest for collaboration among stakeholders towards consensus and commitment may be improved via the use of various group learning and multi-criteria decision-making methods. This study reports the phases, results and implications of an extensive action research project, applying soft systems methodology, which aims to enhance regional forest programmes by facilitating increased use of collaborative decision support methods. Stakeholder feedback from demonstration meetings suggested that discussing alternative futures and prioritizing action proposals in a multi-stakeholder group through a simple multi-attribute rating technique are the most promising immediate enhancements. An ex-post evaluation of the suggested "ideal process model" showed that the deliberative nature of regional forest programmes had strengthened and that strategic and regional choices had become more prevalent in Finnish processes. The evaluation further underlined the need for simple, easily adoptable qualitative methods, but results remained ambiguous regarding potentials of quantitative, aggregative methods. Methodological developments cannot alone unlock central problems of the programme process, namely weak political capital and propensity toward status-quo, but the programme organisation is to be redefined as well.